Transverse Preputial Island Flap for Hypospedias Repair: A Study in A Tertiary Level Hospital - Asad, Hafiz Al; Morshed, Md Selim; Manzer, Tasnim Alam; Hasan, Abu Naser Md Lutful; Chowdhury, Zulfia Zinat; Hosain, AKM Shahadat (Bangladesh Journal of Urology, 2020)
Introduction: Hypospadias continues to be a challenging problem for reconstructive surgeon. As urethral plate preservation got an important role, transverse preputial island flap (TPIF) urethroplasty is one of the preferred technique for sub-coronal and distal penile hypospadius. Methods: This study was conducted at urology department, DMCH, from February, 2014 to June, 2017 where 15 patients underwent TPIF urethroplasty. Inner preputial flap with its pedicle was developed and separated from the dorsal penile skin which was sutured to the urethral plate in an onlay manner over a stent by running suture. Glanuloplasty and meatoplasty was done and skin closed.SPC was done in every cases. Dressing was checked on 5th POD, stent was removed after 03 weeks. SPC was removed 2 to 3 days after satisfactory voiding. All patients were followed up at 6th and 12th week. Results: Among the 15 patients age range was 2-14 years and mean age. Sub-coronal in 4 and distal penile was in 11 patients. Following TPIF urethroplasty wound disruption was noted in one patient for that glans closure was done successfully. There was no meatal stenosis and urethrocutaneous fistula in follow up. Regarding cosmetic outcome 12 were good, 2 were acceptable and 1 was poor. Conclusion: Success rate of TPIF urethroplasty in case of sub-coronal and distal penile hypospadias is excellent. Cosmetic outcome should be considered most challenging and with experience of surgeons this aspect will be improved. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.43-47